Christine de Pizan and biblical wisdom : a feminist-theological point of view - Birk, Bonnie A., 1941- (Marquette studies in theology ;, 2005)
"The fifteen-century writer Christine de Pizan very adeptly used various aspects of the religious traditions of her day in her confrontation of misogynous beliefs and attitudes. In this book the insights of today's feminist scholars in religion are used to demonstrate that one of the more intriguing religious elements Christine drew upon was the female figure of biblical Wisdom."--Jacket